(untitled) (Research, Society and Development, 2021)
One of the ways of insertion of the nutritionist in primary care is through the Expanded Center for Family Health and Primary Care (NASF-AB), thus, this study sought to understand the performance of this professional from the perspective of matrix support (MS) through of an exploratory study, with a qualitative approach, carried out with the nutritionists of the NASF-AB in Tauá/CE. The field research took place in December 2018 using semi-structured interviews. The analysis was carried out using the thematic analysis technique, which made it possible to identify five empirical categories: concept of NASF-AB; team work; incomprehension of MS; MS: care support and pedagogical support; activation of the professional by EqSF; and, challenge and potential for acting at NASF-AB. The analysis showed the gap between central theoretical-practical assumptions and the work process, contributing to the fragmentation of care, distance between professionals, predominance of impersonal referrals and outpatient focused actions, obstacles to interprofessionality and interdisciplinarity, essential conditions for comprehensiveness in health. As a suggestion, carrying out permanent education actions based on MS and its assumptions.